Right Internal Carotid Artery and Basilar Artery Aneurysms After New Coronavirus Infection COVID-19 in Adolescent: Clinical Case - Dina S. Rusinova; Mikhail A. Martakov; Soslan B. Medoev; Ludmila V. Ryzhuk; Vyacheslav V. Yazev (Union of pediatricians of Russia, 2021)
The number of people infected with the SARS-CoV-2 virus causing COVID-19 is steadily growing around the world. Given the fact that the disease is new, it is necessary to study the characteristics of its spreading and clinical course, including pediatric population. The article  presents clinical case of COVID-19 in 15-year-old child with the development of thrombosed basilar artery aneurysm that compressed the brain stem in the pons and subarachnoid hemorrhage, the development of a fusiform aneurysm of the right internal carotid artery. These pathologies were later complicated by right-sided hemiparesis. The importance of inter-clinical interaction of physicians of all specialties and the need for early rehabilitation at the outpatient stage of treatment in the context of the COVID-19 pandemic were shown.